Vigi4Eudra-score: Evaluation of the completeness of spontaneous adverse drug reaction reports in EudraVigilance - Patrick Christ; Diana Dubrall; Dennis Lex; Thomas Grüger; Matthias Schmid; Bernhardt Sachs (PLoS ONE, 2026)
Introduction The vigiGrade completeness score established in VigiBase, the worldwide ADR database, measures the completeness of information provided in the structured format of each ADR report. Currently, no such measurement is implemented in the European ADR database EudraVigilance. The aim of our study was to adjust the algorithm of the vigiGrade completeness score to the structure of the ADR reports from EudraVigilance (=Vigi4Eudra-score). Materials and methods An R script was developed to semi-automatically assess the completeness of structured information provided in the ADR reports extracted from EudraVigilance. The script was applied to four different datasets. We compared the values achieved by the Vigi4Eudra-score to those of the vigiGrade completeness score per ADR report. Results Approximately 15,000 spontaneous reports from the four datasets were assessed. The mean values of the Vigi4Eudra-score of all four datasets ranged from 0.41–0.59. Compared to the values of the vigiGrade completeness score, most commonly, none or only minor discrepancies were found. These were largely attributed to the categories that needed to be adapted for use within EudraVigilance. Conclusions We provide an R script to assess the completeness of information provided in the structured format of ADR reports from EudraVigilance, which may be useful for researchers, pharmaceutical companies, and regulatory authorities. Our use cases demonstrate its successful application.